Laboratory plasma physics experiments using merging supersonic plasma jets. (10th December 2014) - Hsu, S. C.; Moser, A. L.; Merritt, E. C.; Adams, C. S.; Dunn, J. P.; Brockington, S.; Case, A.; Gilmore, M.; Lynn, A. G.; Messer, S. J.; Witherspoon, F. D.
Abstract : We describe a laboratory plasma physics experiment at Los Alamos National Laboratory that uses two merging supersonic plasma jets formed and launched by pulsed-power-driven railguns. The jets can be formed using any atomic species or mixture available in a compressed-gas bottle and have the following nominal initial parameters at the railgun nozzle exit: ne ≈ ni 10 16 cm −3, Te ≈ Ti ≈ 1.4 eV, V jet ≈ 30–100 km/s, mean charge Z ≈ 1, sonic Mach number Ms ≡ V jet / Cs > 10, jet diameter = 5 cm, and jet length ≈20 cm. Experiments to date have focused on the study of merging-jet dynamics and the shocks that form as a result of the interaction, in both collisional and collisionless regimes with respect to the inter-jet classical ion mean free path, and with and without an applied magnetic field. However, many other studies are also possible, as discussed in this paper.